Pengaruh Loneliness, Self Control Dan Work Environment Terhadap Cyberloafing Pada Karyawan Café A.F Ruang Rindu Kabupaten Mamuju - Rahmatunnisa, Laila; Aqil, Muhammad; Rasyid, Rohsita Amalyah; Junaeda, Junaeda; Arsyad, Muhammad (Pascasarjana Universitas Muhammadiyah Mamuju, 2025)
This study aims to determine the effect of loneliness self control and work environment on cyberloafing in employees of Cafe A.F Rindu Rindu Mamuju District. This study uses a type of quantitative method, with a population of 32, determining the sample size using total sampling because the number of respondents is 32 so that the entire population is used as a sample in this study. The data collection techniques used in this study were observation, questionnaires and interviews. Testing the quality of research instruments using validity tests and reliability tests. Data analysis tools used multiple linear regression analysis, hypothesis testing using partial test (t test), simultaneous test (f test) and to determine the contribution of independent variables to the dependent variable used detrmination coefficient test (R2 test). The results showed (1) loneliness has no effect on cyberloafing partially, (2) self control has no effect on cyberloafing partially, (3) work environment has a partial effect on cyberloafing, and (4) loneliness self control and work environment have a simultaneous influence on cyberloafing. Then for the contribution of loneliness, self-control and work environment to cyberloafing is classified as strong with a percentage of 62.1%, this means that other predictor variables of 37.9% which are not explained in this study have the ability to increase cyberloafing in employees of Cafe A.F Ruang Rindu Mamuju District